The effect of robotization in OECD countries on Latin American exports - Andreas Baur; Lisandra Flach; Isabella Gourevich (EconPol Forum, 2022)
The effects of automation in high-income countries are not limited to domestic economies, but might spill over via global supply chains. We evaluate the effects of robot adoption in OECD countries on exports from Latin America to the OECD along the value chain. We combine detailed firm-level data for four Latin American countries with data on robot adoption and input-output linkages. In response to robot adoption, exports in the same industry decrease, but exports increase for products along the value chain. Our results indicate the importance of evaluating supply chain linkages when drawing policy conclusions about the effects of robotization
Keywords: 330